Taxonomy of sympatric New Zealand species of Platynereis, with description of three new species additional to P. australis (Schmarda) (Annelida: Polychaeta: Nereididae) - Read, Geoffrey B. (Zootaxa, 2007)
Metamorphosed, sexually mature Platynereis adults captured swimming nearshore at night off the New Zealand coast had major morphological differences that indicated four similar sympatric species existed, where previously only P. australis had been known. Simultaneous reproductive swarming of all taxa was possible at a locality. The three hitherto cryptic species are described as Platynereis mahanga sp. nov., P. kau sp. nov., and P. karaka sp. nov.. Paragnath arrangement and chaetal morphology are near identical in all four species. Homogomph notopodial falcigers, which are distinctive in shape in some Platynereis, are lacking in adults of this group of species. Pigmentation pattern differences and other minor variations are present in life in atokous (unmetamorphosed) benthic forms, but museum specimen atokes cannot be unambiguously separated into species by morphology. Heteronereid (metamorphosed) natatory forms of the four New Zealand species are distinct in several characters, including morphology of sperm papillae groups in males, and number of pre-natatory anterior segments in both sexes. Differences in size, habitat, peak spawning season, interbreeding, and juvenile development are noted. Morphology and biology are discussed in relation to other Platynereis. Presence of the P. australis group species beyond the continental shelf seas adjoining the three main islands is now undetermined except for P. australis at Chatham Islands, P. mahanga at the subantarctic Auckland and Campbell Islands, and P. karaka at Wanganella Bank; all prior reports of P. australis outside the New Zealand region need re-evaluation from specimens.